PERANCANGAN REMOTE KONTROL UNTUK MENGENDALIKAN LAMPU PENERANGAN DENGAN MENGGUNAKAN SINYAL INFRA MERAH - Sudirman S; Daniel Adutae; Sri Kurniati A (Jurnal Media Elektro, 2012)
Generally installation of lighting applies manual switches to turn-on and turn-off the light electricity through connection cable. This system besides less efficiently also able to generate voltage shoot or losses energy if lamp distance with rather far linkage switches. More than anything else if there are any diffuse joint, hence can result heating generating over current, even can cause burning.This paper aim to make a controller device by using infrared. Remote infrared control can replace function of switches that is commonly use at installation of lighting without using connection cable. Planning of this device done by using data signal 660 Hz while signal carrier applies frequency 40 Khz. Result of gauging of oscilloscope at data frequency is obtained by gauging of 666,67 Hz or there is difference around 1.01 %. Then at generator carrier is obtained by gauging of frequency around 41.67 Khz or there is difference around 4.18 %. Result of assaying of device indicates that remote control has functioned carefully as according to what planned, that is can turn-on and tirn-off lighting without using switches. Lamp controller can be put accross comes up with distance 9 meter with acceptance angle 0 - 20 degrees.